A pharmacovigilance study of the association between linaclotide/plecanatide and muscle spasms based on food and drug administration adverse event reporting system - Fan, Xue; Li, Yuan; Lin, Xiangchun (Frontiers in Pharmacology, 2025)
BackgroundLinaclotide and plecanatide, as guanylate cyclase-C agonists, are effective treatments for irritable bowel syndrome with constipation and chronic idiopathic constipation. While their therapeutic benefits are well-established, the potential association between these drugs and the adverse reaction of muscle spasms remains understudied and controversial.AimTo evaluate the potential association between muscle spasms and linaclotide or plecanatide using real-world pharmacovigilance data.MethodCases of muscle spasms linked to linaclotide or plecanatide as primary suspected drugs were extracted from the Food and Drug Administration Adverse Event Reporting System (FAERS). Disproportionality analyses, including reporting odds ratio and information component, were employed to detect safety signals. Temporal patterns were assessed using Weibull distribution analysis.ResultsA total of 231 muscle spasms cases were identified (linaclotide: 182; plecanatide: 49). Females accounted for 72.3% of the cases (n = 167), indicating a higher susceptibility. Disproportionality analysis revealed significant safety signals for both drugs, with plecanatide showing a stronger association (ROR = 6.12, 95% CI: 4.61–8.11) compared to linaclotide (ROR = 1.88, 95% CI: 1.63–2.18). Weibull analysis demonstrated an early failure-type curve (β < 1), suggesting a higher incidence shortly after treatment initiation.ConclusionThis study identifies a significant association between linaclotide/plecanatide and muscle spasms. The findings highlight the need for vigilance in high-risk populations and call for further investigation into the underlying mechanisms.